Differing visions of a learning society : research findings. - Coffield, Frank (Policy Press, 2000)
This second volume discusses both the meaning of the Learning Society for adults with learning difficulties, and the use of social capital to explain patterns of lifelong learning. It presents five different 'trajectories' of lifelong learning, and it explores determinants of participation and non-participation in learning, and innovation, in higher education.